PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI MENGGUNAKAN ANIMAKER PADA MATERI STATISTIKA - Helmi Ilham Nabila; Nelly Fitriani; Wahyu Setiawan (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The aim of the investigation is to create practical and efficient mathematics learning media for classroom use using animaker-animated videos. The ADDIE model, comprising five stages, namely Analysis, Design, Development, Implementation, and Evaluation, was employed to carry out the Research and Development (RD) method. The study was conducted at SMP Negeri 1 Margaasih, with ten ninth-grade students involved in a small-scale trial and 36 ninth-grade students in a large-scale trial. The validators were media experts, material experts, and math teachers. Microsoft Excel was utilized to assess the average response of students based on a feedback questionnaire. The outcomes revealed that the product was in line with the ADDIE research method, with a product feasibility of 84% for media experts, 65% for material experts, and 77% for teachers in the small-scale trial, and 96% for media experts, 87% for material experts, and 94% for teachers in the large-scale trial, indicating that it is highly feasible. The validated products were then tested on students through small and large-scale trials, with 87% showing very practical criteria.